Phytochemical analysis, in-vitro and in-silico study of antiproliferative activity of ethyl acetate fraction of Launaea cornuta (Hochst. ex Oliv. & Hiern) C. Jeffrey against human cervical cancer cell line - Lagu, Inyani John Lino; Nyamai, Dorothy Wavinya; Njeru, Sospeter Ngoci (Frontiers in Pharmacology, 2024)
Introduction: Cervical cancer is one of the leading causes of death among women globally due to the limitation of current treatment methods and their associated adverse side effects Launaea cornuta (Hochst. ex Oliv. & Hiern) C. Jeffrey is used as traditional medicine in the treatment of a variety of diseases, including cancer. Objective: This study aimed to evaluate the selective antiproliferative, phytochemical profiles, and antimigratory effects of L. cornuta and to explore the modes of action in human cervical cancer cell lines (HeLa-229). Materials and Methods: The cytotoxic effect of L. cornuta ethyl acetate fraction on the proliferation of cervical cancer cells was evaluated by MTT assay. Compounds were analysed using the quantitative colour method and gas chromatography-mass spectroscopy (GC-MS). Subsequently, bioinformatic analyses were performed to screen for potential anticervical cancer and therapeutic target genes of L. cornuta. MD was performed to predict and understand the molecular interactions and molecular mechanisms of the ligands against cervical cancer. A reverse transcription-quantitative polymerase chain reaction was performed to validate the network analysis results. Results: L. cornuta ethyl acetate fraction exhibited a remarkable cytotoxic effect on HeLa proliferation (IC50 of 20.56±2.83 µg/mL) with a selectivity index (SI) of 2.36 without affecting Vero cells (IC50 of 48.83±23.02). Thirteen compounds were identified by GC-MS analysis. 124 potential target genes associated with the effect of L. cornuta ethyl acetate fraction on human cervical cancer were obtained, including AKT1, MDM2, CDK2, MCL1 and MTOR, identified among the top hub genes and PI3K/Akt1, and Ras/MAPK pathways identified as the significantly enriched pathways. Molecular docking results showed that stigmasteryl methyl ether had a high binding affinity against CDK2, ATK1, BCL2, MDM2, and Casp9, with binding energy ranging from -7.0 to 12.6 kcal/mol. Tremulone showed a good binding affinity against TP53 and P21 with -7.0 and 8.0 kcal/mol, respectively. RT-qPCR analysis revealed that CDK2, MDM2, and BCL2 were down-regulated, and Casp9 and P21 were up-regulated in HeLa cells treated with L. cornuta compared to the negative control. Conclusions: The findings indicate that L. cornuta ethyl acetate fraction phytochemicals targeting various targets and pathways exhibit selective cytotoxic effects against HeLa cells.